2013
DOI: 10.1111/ina.12025
|View full text |Cite
|
Sign up to set email alerts
|

People who live in a cold climate: thermal adaptation differences based on availability of heating

Abstract: Are there differences in thermal adaptation to cold indoor environments between people who are used to living in heating and non-heating regions in China? To answer this question, we measured thermal perceptions and physiological responses of young men from Beijing (where there are indoor space heating facilities in winter) and Shanghai (where there are not indoor space heating facilities in winter) during exposures to cold. Subjects were exposed to 12°C, 14°C, 16°C, 18°C, 20°C for 1 h. Subjects from Beijing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 12 publications
3
26
0
3
Order By: Relevance
“…One of the key findings was that students who migrated from southern China to attend university in northern China took a year to adapt to their new indoor thermal environment. Yu [25] demonstrated in climate chamber experiments that residents who were used to cold indoor climate had better physiological response than those always lived in warm indoors when they were exposed to cold temperatures. All these studies offer some sketchy evidences relating to changing thermal comfort expectations, from various angles.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…One of the key findings was that students who migrated from southern China to attend university in northern China took a year to adapt to their new indoor thermal environment. Yu [25] demonstrated in climate chamber experiments that residents who were used to cold indoor climate had better physiological response than those always lived in warm indoors when they were exposed to cold temperatures. All these studies offer some sketchy evidences relating to changing thermal comfort expectations, from various angles.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…A further study by Yu et al [20] investigated the long term impact of access to indoor heating on levels of physiological response by considering sub groups from Shanghai and Beijing separately. This is based on Chinese legislation which stipulates that indoor heating systems be installed only if more than 90 days in the year see a mean air temperature of 5 •C or less [20]; Beijing does fall under this category and thus indoor heating is common whereas Shanghai does not.…”
Section: B)mentioning
confidence: 99%
“…This is based on Chinese legislation which stipulates that indoor heating systems be installed only if more than 90 days in the year see a mean air temperature of 5 •C or less [20]; Beijing does fall under this category and thus indoor heating is common whereas Shanghai does not. This study presented 2 significant findings: (i) the skin temperature of the participants from Shanghai decreased faster than those from Beijing, which indicates a greater degree of vasoconstriction and (ii) participants from Beijing presented significantly more instances of shivering, which implies that they require more extreme homeostatic mechanisms to maintain core body temperature [20]. Since Shanghai experiences warmer winters than Beijing and therefore has no indoor heating, these findings suggest that indoor thermal history is more significant than outdoor thermal history in determining physiological acclimatisation [20].…”
Section: B)mentioning
confidence: 99%
“…Complementing this body of field-based evidence is the climate chamber study by Yu [17] who compared the lowest acceptable temperature between residents living in Shanghai (HSCW climate without district heating) and Beijing (Cold climate with district heating). It was found that the lower 80% acceptable temperature in Shanghai (16.3 C) was 2.5 C lower than that observed in Beijing (18.8 C).…”
Section: Introductionmentioning
confidence: 99%